PERSEPSI DAN KEPUASAN KONSUMEN TERHADAP PRODUK LOKAL KHAS BANTEN DI KAWASAN WISATA ANYER - Meutia Meutia; Khaerul Saleh; Mochammad Idham Maulana (Leuit (Journal of Local Food Security), 2020)
Perception is a response or finding a direct picture of a finding or direct description of a person and absorption in knowing some things through the five senses, and satisfaction is the feeling of being happy or disappointed someone who appears after comparing between perceptions / impressions of the performance or results of a product and expectations - The aim of this research is to analyze consumer perceptions and consumer satisfaction with Banten local food products by tourists on the Anyer beach. The method used in this study is quantitative descriptive method. With the sampling technique used is accidental sampling and purposive sampling. The location is determined precisely at Anyer beach tourist location. The analytical method used in this study is the importance performance analysis and customer satisfaction index method using the SPSS software program (Statistical Package for Social Since). Based on the descriptive analysis, consumer characteristic of the consumer at Anyer beach tourist is dominated by male respondent, aged 26-35 years, marital status married, the last education is Bachelor, private sector worker, and average income valued at Rp.3.000.000 – Rp.6.000.000. Based on analysis of Customer Satisfaction Index (CSI) is 78,15 percent.